La muerte de la buena fe registral - Escobar Rozas, Freddy (2015)
The article 2014 of the Civil Code has been recently modified.  In  order  to  make this decision, the legislator took in consideration two reasons: theaffirmation that the record entry doesn’t countswith its own substantivity, and that the necessityof adopting measures to fight against fraudulentacts that might affect the owners.Following this modification, the author presents a comparative analysis of the before and after of the option the legislator took, and takes position after putting himself in the side of third parties. From a juridical and economical point of view, he studies the modification and concludes that, apart from not resolving the problems it had to solve, generates damages that affect the third parties and the market.